2010
DOI: 10.1007/s10344-009-0356-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Iberian ibex (Capra pyrenaica) sperm quality and level of parasitism

Abstract: This paper examines the relationship between parasite infection rates and reproductive function in wild Iberian ibexes. The animals examined were 43 adult males shot during the rutting season. Gastrointestinal and pulmonary nematodes, intestinal cestodes and intestinal coccidia were determined by coprological analysis. Protozoa in the muscles were detected by biopsy. Epididymal spermatozoa were collected from recovered testes. Sperm motility, the integrity of the plasma membrane, sperm viability, sperm morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…What little data concerning wild mammals that exists generally deals with female fecundity (Iason and Boag, 1988;Pence and Windberg, 1994;Neuhaus, 2003;Pioz et al, 2008) or host behavior (Cramer and Cameron, 2007) and there are enormous gaps in our knowledge regarding the effects of parasites on the testes of wild mammals. Recently, Santiago-Moreno et al (2010) examined the relationship between sperm quality and the level of parasitism in Iberian ibex. Nevertheless, all animals examined in their study were selectively hunted for their relatively small horn development and individual phenotypic quality was not considered in their analysis as a potential confounding factor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…What little data concerning wild mammals that exists generally deals with female fecundity (Iason and Boag, 1988;Pence and Windberg, 1994;Neuhaus, 2003;Pioz et al, 2008) or host behavior (Cramer and Cameron, 2007) and there are enormous gaps in our knowledge regarding the effects of parasites on the testes of wild mammals. Recently, Santiago-Moreno et al (2010) examined the relationship between sperm quality and the level of parasitism in Iberian ibex. Nevertheless, all animals examined in their study were selectively hunted for their relatively small horn development and individual phenotypic quality was not considered in their analysis as a potential confounding factor.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, all animals examined in their study were selectively hunted for their relatively small horn development and individual phenotypic quality was not considered in their analysis as a potential confounding factor. Also, despite some determining factors of testis traits have nonlinear effects and despite testis traits are governed simultaneously by multiple factors (Sarasa et al, 2010b), the most highlighted analysis in the study of Santiago-Moreno et al (2010) looked separately for linear relationships. Moreover, only one from the six sperm variables considered showed a weak relationship with one from the five parasitic classes considered (Santiago-Moreno et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many ungulates, males expend a substantial part of their fat reserve in the autumn rut. Less energy available for allocation to immune defense [ 44 , 45 ] together with adverse effects of testosterone [ 46 - 49 ] is the most likely explanation for the higher susceptibility of reproductively active males to pathogens. In chamois, increased susceptibility to scabies in sexually active males, as indicated by lower survival of these males in populations affected by scabies (Figure 4 ), is thus likely linked to their exhaustive depletion of energy reserves during the early-winter rut when they defend mating territories and compete heavily for access to females [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various serological studies have shown antibodies against Sarcocystis sp. (Granados et al 2001;Antón et al 2002;Luzón et al 2008;Santiago-Moreno et al 2010), Babesia sp. (Ferrer et al 1998;García-Moreno et al 2009), Toxoplasma gondii, and Neospora caninum (Gauss et al 2006;Almería et al 2007;García-Bocanegra et al 2012).…”
Section: Fasciola Hepatica and Dicrocoeliummentioning
confidence: 99%